Differential expression of Bcl-2 protein in non-irradiated or UVC-irradiated murine myleoid leukaemia (ML) cells - Popović-Hadžija, Marijana (Radiology and oncology (Ljubljana), 1998)
In this work, we examined the expression of Bcl-2 protein in myueloid leukaemia (ML) cells and the effect of UVC-light on the expression level. The protein of bcl-2 oncogene was detected by immunocytochemical method. In spleencells of healthy RFM donors was detected 34.3% of Bcl-2 positive cells. When leukaemia came to the non terminal phase (NTP) more than 50% of cells expressed this protein. However, in terminal phase (TP) of leukaemia growth, only 24.4% Bcl-2 positive cells was determined. After UVC irradiation, the expression of Bcl-2 protein was significantly higher in spleen cells of healthy donors. However, UVC light did not change the expression of Bcl-2 in cells of both investigated phases of ML growth. Bcl-2 protein may be involved in the resistance of ML cells to UVC light.
Keywords: Genes, bcl-2; Immunology; Leukemia, myeloid; Mice; Proto-oncogene proteins c-bcl-2; Spleen; Ultraviolet rays